Application of masking technique in EDM for generation of rectangular shaped pattern. (2015) - Rahang, Maneswar; Patowari, Promod Kumar
This paper presents a novel application of masking technique for pattern generation in electric discharge machining (EDM). The experimental study was carried out to explore the capability of pattern generation using shaped masking and simple flat end tool electrode without any pattern on it. Powder metallurgical (P/M) green compacts of composition 75%W-25%Cu were used as tools and aluminium as work material. Powder materials were deposited at pre-defined area of work surface to generate some rectangular block pattern. Deviation from pre-defined boundary line was observed to analyse the geometric dimensional accuracy. Experimental results showed that compact load plays very important role followed by peak current (Ip ) and pulse on-time (Ton ) over the surface roughness and edge roughness of the pattern. At optimum condition, surface roughness was found to be 3.17 µm and edge roughness to be 6.42 µm. SEM, EDS and XRD analyses confirmed tool material transfer to pre-defined area.